The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.virol.2008.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for cell rounding and surface protein down-regulation by Ebola virus glycoprotein

Abstract: Ebola virus causes an acute hemorrhagic fever that is associated with high morbidity and mortality. The viral glycoprotein is thought to contribute to pathogenesis, though precise mechanisms are unknown. Cellular pathogenesis can be modeled in vitro by expression of the Ebola viral glycoprotein (GP) in cells, which causes dramatic morphological changes, including cell rounding and surface protein down-regulation. These effects are known to be dependent on the presence of a highly glycosylated region of the gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 47 publications
8
50
0
Order By: Relevance
“…We tested the effect of GP tagged with the endoplasmic reticulum (ER) retention motif, KKMP. This mutant is efficiently retained in the ER, with minimal surface expression as determined by immunofluorescence microscopy and flow cytometry (18). GP-KKMP failed to restore tetherin-restricted VLP budding, despite ample expression of the GP in cell lysates (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…We tested the effect of GP tagged with the endoplasmic reticulum (ER) retention motif, KKMP. This mutant is efficiently retained in the ER, with minimal surface expression as determined by immunofluorescence microscopy and flow cytometry (18). GP-KKMP failed to restore tetherin-restricted VLP budding, despite ample expression of the GP in cell lysates (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Some studies have indicated that GP 1,2 induces active internalization of surface molecules required for attachment and communication with the immune system and also promotes cell death (51,52). Other studies have suggested that GP 1,2 sterically occludes surface factors without actually reducing cell viability (20,53). In one study, it was reported that overexpression of GP 1,2 , through mutation of the GP editing site, resulted in enhanced cytopathicity, with the recombinant virus growing to lower infectivity titers (19).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that EBOV GP 1,2 is metabolically costly to synthesize and process and that high levels of GP 1,2 expression are toxic to host cells (18,19). While the exact mechanism of toxicity has been debated, it has been observed that overexpression of GP 1,2 leads to cell rounding and detachment as well as loss of detection of some cell surface markers (20)(21)(22). Importantly, EBOV regulates GP 1,2 expression via an RNA-editing mechanism whereby full-length GP 1,2 mRNA is produced by slippage of the viral polymerase at an editing site (23,24).…”
mentioning
confidence: 99%
“…Such effects could even be something that GP does as a contribution to the Ebola virus assembly process. In support of such a scenario, GP has recently been reported to impede the recognition of several cell surface proteins, including ␤1 integrin (CD29) and major histocompatibility complex (MHC) class I (84,87,95), through a mechanism of glycan-mediated steric hindrance (20,76). However, the mucin-like domain of GP that is necessary for this effect (20) is not required for GP to counteract tetherin (44).…”
Section: Discussionmentioning
confidence: 99%